A new poly-Si TFT compensation pixel circuit employing AC driving mode for AMOLED displays - 宋小锋 罗建国 周雷 张立荣 吴为敬 彭俊彪 (Journal of semiconductors, 2013)
This paper presents a new poly-Si pixel circuit employing AC driving mode for active matrix organic light-emitting diode （AMOLED） displays. The proposed pixel circuit, which consists of one driving thin-film tran- sistor （TFT）, three switching TFTs, and one storage capacitor, can effectively compensate for the threshold voltage variation in poly-Si and the OLED degradation. As there is no light emission, except for during the emitting period, and a small number of devices used in the proposed pixel circuit, a high contrast ratio and a high pixel aperture ratio can be easily achieved. Simulation results by SMART-SPICE software show that the non-uniformity of the OLED current for the proposed pixel circuit is significantly decreased （〈 10%） with an average value of 2.63%, while that of the conventional 2T1C is 103%. Thus the brightness uniformity of AMOLED displays can be improved by using the proposed pixel circuit.